Street Children in Nepal: Causes and Health Status - Sharma, Mohan Kumar (Journal of Health Promotion, 2020)
Street children refer to the children who have not reached adulthood, for whom the street has become their habitual abode and/or a source of livelihood. The reasons for their connection to the street will vary from nation to nation, city to city, and from person to person. This research envisaged to explore the causes of being street children and assess their health status of two study areas, Kathmandu and Birjung, Nepal. The research followed descriptive, exploratory and applied 'QUAN-qual', quantitative dominant mixed methods. The two: semi-structured questionnaire with 150 participants for quantitative data and Key-in-depth interviews (KIIs) with 18 participants for qualitative data were employed in this research. The research areas were purposively selected as per the researcher's pre-observation and respondents on the basis of convenience sampling. The quantitative data were analyzed using the Statical Package for the Social Science (SPSS) software version 20.0 and qualitative data were thematically analyzed using content analysis. The findings of the study depicted that the dominant causes to be street children are family-based causes. Economic, social, and other causes are second, third, and fourth respectively in the study area. Additionally, gender and alcohol consumed behavior was found significant where education level and age had no significance to determinants of the health status of street children. The overall implication of the study signifies that the attention has been shifted from treating the biological to encouraging street children to gain positive necessary health skills that are based on self-care and self-management behaviors including knowledge, beliefs, attitude, motivation, and behaviors.